اتجاهات أساتذة السنة أولى ابتدائي نحو التدريس بمهارات الوعي الصوتي في نشاط القراءة - شيخاوي عمر; شريفي حليمة (University of Eloued جامعة الوادي, 2024)
Abstract: Summary: The current study aimed to know the attitudes of first-year primary school teachers towards teaching phonological awareness skills in reading activity. Using the descriptive approach, and applying the attitudes of first-year primary school teachers towards teaching phonological awareness skills in the reading activity, prepared by the researchers, on a sample of (52) first-year primary school teachers, in Educational District No. 62 in M’Sila Province - Algeria - during the school year (2023-2024); the results showed the following: - There are positive attitudes among first year primary school teachers towards teaching phonological awareness skills in reading activity. - There are no statistically significant differences between the averages of the attitudes of first-year primary school teachers towards teaching phonemic awareness skills in reading activity, due to the variable of professional experience - There are no statistically significant differences between the averages of the attitudes of first-year primary school teachers towards teaching phonological awareness skills in the reading activity, due to the academic qualification variable. ملخص: هدفت الدراسة الحالية إلى معرفة اتجاهات أساتذة السنة أولى ابتدائي نحو التدريس بمهارات الوعي الصوتي في نشاط القراءة. باستخدام المنهج الوصفي، وتطبيق اتجاهات أساتذة السنة أولى ابتدائي نحو التدريس بمهارات الوعي الصوتي في نشاط القراءة ، الذي أعده الباحثان، على عينة قوامها (52) من أساتذة السنة أولى لمرحلة التعليم الإبتدائي، بالمقاطعة التربوية رقم 62 بولاية المسيلة –الجزائر- خلال السنة الدراسية (2023-2024)، أظهرت النتائج ما يلي: - وجود اتجاهات ايجابية لدى أساتذة السنة أولى ابتدائي نحو التدريس بمهارات الوعي الصوتي في نشاط القراءة. - لا توجد فروق ذات دلالة إحصائية بين متوسطات اتجاهات أساتذة السنة أولى ابتدائي نحو التدريس بمهارات الوعي الصوتي في نشاط القراءة، تعزى لمتغير الخبرة المهنية. - لا توجد فروق ذات دلالة إحصائية بين متوسطات اتجاهات أساتذة السنة أولى ابتدائي نحو التدريس بمهارات الوعي الصوتي في نشاط القراءة، تعزى لمتغير المؤهل العلمي لكلمات المفتاحية: الاتجاه؛ مهارات الوعي الصوتي. نشاط القراءة.
دراسة ميدانية، بالمقاطعة التربوية 62 بولاية المسيلة؛ الجزائر
Keywords: trend; Phonemic awareness skills; Reading activity; الاتجاه; مهارات الوعي الصوتي; نشاط القراءة